Evaluation of the Adsorptive Process on Adsorbent Surfaces as a Function of Pressure in an Isosteric System Compared with Adsorption Isotherm - Sindisiwe Ntsondwa; Velaphi Msomi; Moses Basitere (ChemEngineering, 2022)
The developing significance of adsorption has brought about a steadily expanding quantity of logical and innovative writing on different adsorbents. This paper intends to propose experimental and computational methods for measuring the strength of adsorbate–solid interactions. It primarily focuses on the use of graphs to measure the effectiveness of an adsorbate’s bonds with the solid adsorbent by determining the isosteric heat. The Clausius–Clapeyron model equation is used to determine the isosteric enthalpy of adsorption from two adsorption isotherms at various but close temperatures, with ΔT of 10 °C. A full computational explanation of the Clausius–Clapeyron model equation for determining ΔHads is provided using experimental data. Logarithmic plots of uptakes vs. p in the low-pressure zone for the Freundlich–Langmuir graph are used to assess and confirm the quality of the crucial underlying isotherms. The isosteric heat was found to be between 13.5 kJ/mol and 16 kJ/mol.